Clinical effectiveness of hemodiafiltration in elderly patients with uremia - GAO Lu; YE Li-ping; CHENG Wei; GU Jin; LEI Ting (Linchuang shenzangbing zazhi)
Objective To study the clearance of uremia toxins,the tolerance of dialysis,and clinical effectiveness of hemodiafiltration（HDF） in elderly patients with uremia.Methods Thirtyeight cases of uremic patients undergoing maintenance hemodialysis（MHD）,and randomly divided into HDF group and HD group according to the economic situatioa HDF group was given HDF one time every week and HD twice every week,and HD group given HD three times every week.HD programs in two groups were the same.During an observation period of three months,urea clearance index（Kt/V）,serum creatinine（SCr）,blood urea nitrogen（BUN）,uric acid（UA）,β2-microglobulin（β2-MG）,parathyroid hormone（iPTH）,potassium,calcium,phosphorus,carbon dioxide combining power（CO2-CP） descent rate and treatment of complications and incidence of adverse reactions were observed.Results HDF patients had better tolerance than those of HD.The rate of dialysis was significantly less in HDF group than in HD group（P<0.01）.The clearance of β2-MG and iPTH was higher in HDF group than in HD group.KT/V was increased greatly in HDF group.BUN,SCr and serum UA were decreased significantly after the treatment as compared with those before treatment,but there was no statistically significant difference between two groups.After treatment,serum potassium,calcium,phosphorus and CO2-CP were significantly decreased,and acid-base balance disorders were significantly corrected in both two groups（P<0.01）,but there was no statistically significant difference between two groups.Conclusions The clearance rate of all sizes of uremic toxins was significantly higher by HDF + HD than by HD.HDF increased the tolerance to dialysis and significantly improved the effect of dialysis,suitable for easy to appear hemodialysis complication and uncomfortable symptoms of uremia patients.